2012
DOI: 10.1111/j.1742-481x.2012.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot wounds in haemodialysis patients: 2‐year outcome after percutaneous transluminal angioplasty and minor amputation

Abstract: Critical limb ischaemia (CLI) is known to be associated with high mortality. In some patients, surgery cannot be performed due to high risk of perioperative death and complications. In other cases, there is only pain at rest but no wound. Therefore, it is difficult to accurately predict the prognosis of individual patients. We examined the prognosis of CLI cases in which therapeutic footwear was made for ambulation after wounds healed. The subjects were 31 haemodialysis patients with diabetic foot wounds, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Even though PTA is considered a possible procedure to treat critical limb ischemia, there is limited literature available on the prognosis of this intervention. In a 2-year follow-up prospective study on haemodialysis patients with diabetic foot wounds who were treated with PTA and minor amputation, it was found that only 41.9% of patients survived without reamputation with a 2-year postoperative mortality rate of 38.7% [ 29 ]. This study had a small sample size of 31 haemodialysis patients; hence, it is important to explore the prognosis of PTA as treatment and prevention of amputation by doing more studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PTA is considered a possible procedure to treat critical limb ischemia, there is limited literature available on the prognosis of this intervention. In a 2-year follow-up prospective study on haemodialysis patients with diabetic foot wounds who were treated with PTA and minor amputation, it was found that only 41.9% of patients survived without reamputation with a 2-year postoperative mortality rate of 38.7% [ 29 ]. This study had a small sample size of 31 haemodialysis patients; hence, it is important to explore the prognosis of PTA as treatment and prevention of amputation by doing more studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the patients use therapeutic shoes, one in three will have recurrent foot wound and will undergo reoperation. In other words, only two in five patients survive two years after minor amputation with no recurrent wounds that require an operation 10) . The frequency of reamputation is known to be higher after toe amputation as compared with that after mid-foot amputation 11) .…”
Section: Discussionmentioning
confidence: 99%
“…A report examining the prognosis after minor amputation reported that 31.5% patients required reamputation within 2 years [3]. These reports indicate that amputees are older and have a higher shortterm reamputation rate.…”
Section: Introductionmentioning
confidence: 99%